High-Q dual-band graphene absorbers by selective excitation of graphene plasmon polaritons: Circuit model analysis. (December 2020) - Barzegar-Parizi, Saeedeh; Ebrahimi, Amir; Ghorbani, Kamran
Highlights: Designing THz dual-band absorbers based on graphene patterned arrays. Derivation of closed-form relations for the parameters using an analytical model. Simplicity of the structure in comparing to the previous proposed absorbers. Higher quality factor in comparison to other graphene-based dual-band absorbers. More absorption stability with respect to the oblique incidence angles. Abstract: This article presents the design of two dual-band graphene-based absorbers for terahertz frequencies. The absorbers are composed of two-dimensional (2D) arrays of ribbons and disks printed on a ground plane backed dielectric spacer. The design is based on the excitation of a specific plasmon polariton of the graphene patterned array at each resonance band. An analytical circuit model is used to derive closed-form relations for the geometrical parameters of the absorber and graphene parameters. The graphene patterned array appears as a surface admittance made of an infinite parallel array of series RLC branches. Each branch is equivalent to a graphene plasmon polariton (GPP) providing a distinct resonance mode. The design procedure is based on selectively exciting the first two GPPs. This means that two of the parallel RLC branches are selectively used in the circuit model analysis. The results obtained using the analytical solution are compared with the full-wave simulations in HFSS. The agreement between the results validates the developed design method.